2011
DOI: 10.1002/pon.1814
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden among poor caregivers of patients with cancer in an urban African setting

Abstract: The study demonstrated a high level of caregiver burden, psychological morbidity and financial strain in family caregivers coming to the clinic with a relative who has cancer in an urban Nigerian setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 11 publications
5
63
2
1
Order By: Relevance
“…Some categories of this concept, that is, patient-related stress, concern about future, stress, depression and grief, financial and physical problems, family challenges, sleep-related changes, psychological functional problems, loneliness and caregiving pressure are consistent with some research (4,7,8,(14)(15)(16)(17)(18). However, two sub-categories, namely, annoying and dysfunctional beliefs and resentment from the relatives are not seen in prior research.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Some categories of this concept, that is, patient-related stress, concern about future, stress, depression and grief, financial and physical problems, family challenges, sleep-related changes, psychological functional problems, loneliness and caregiving pressure are consistent with some research (4,7,8,(14)(15)(16)(17)(18). However, two sub-categories, namely, annoying and dysfunctional beliefs and resentment from the relatives are not seen in prior research.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, cancer is a familial disease which goes beyond the patient itself (3). The nature and severity of the problems affecting the caregivers are unknown in the developing countries, and such individuals have been called as the hidden patients (4). Hence, screening the needs and psychological pressures among family members of cancer patients is a vital and important matter in all the phases of this disease (5).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that care burden of the average 18.5-29.16 (Grunfeld et al, 2004;İnci, 2006;Higginson and Gao, 2008;Higginson et al, 2009;Yusuf et al, 2010). The reported mean Burden Interview score of caregivers for this study was higher in comparison to those stated in literature.…”
Section: Discussioncontrasting
confidence: 57%
“…Examples of common psychological consequences of caregiving include distress, anxiety, anger, and depression among others [12][13][14]. Specifically, studies have identified a bi-directional relationship between caregiving burden and psychological distress among patients with various chronic medical illnesses [13,15,16]. Unfortunately, while caregiver burden has been extensively examined in relation to many chronic illnesses [15][16][17][18][19], there appears to be none among caregivers of children with OAT.…”
mentioning
confidence: 98%